Effects of preheating on briquetting and subsequent hydrothermal pretreatment for enzymatic saccharification of wheat straw. (28th March 2019) - Gong, Chunxiao; Thomsen, Sune Tjalfe; Thygesen, Lisbeth G.; Felby, Claus
Abstract: Briquetting of plant biomass with low bulk density is an advantage for handling, transport, and storage of the material, and heating of the biomass prior to the briquetting facilitates the densification process and improves the physical properties of the briquettes. This study investigates the effects of preheating prior to briquetting of wheat straw (WS) on subsequent hydrothermal pretreatment and enzymatic conversion to fermentable sugars. WS (11% moisture content) was densified to briquettes under different conditions; without preheating or with preheating at 75 or 125°C for either 5 or 10 min. Subsequent hydrothermal pretreatment was done for both un‐briquetted WS and for briquettes. Enzymatic saccharification was afterwards performed for all samples. The results showed that as expected, nonpretreated WS briquettes gave very low sugar yields (22–29% of the cellulose content), even though preheating at 125°C prior to briquetting (without pretreatment) improved sugar yields somewhat. When combined with pretreatment, briquetting with preheating showed neutral or negative effects on sugar yield. This result suggests that moderate preheating (75°C for 5 min) before briquetting improved bulk density and compressive resistance of briquettes without impeding subsequent enzymatic conversion. However, excessive preheating (75 or 125°C for 10 min) before briquetting may result in irreversible structural modifications that hinder the interaction between biomass and water during pretreatment, thereby decreasing the accessibility of cellulose to enzymatic saccharification.